Program Evaluation of Continuing Professional Development at Teacher Working Group - Zainuddin, Zainuddin; Suryadi, Suryadi; Fuad, Nurhatati (Universitas Malikussaleh, 2019)
The aims of the study is to evaluate implemention of the continuing professional development program in Teacher Working Group at antecedent, transaction, and outcomes levels.The paper is an qualitative studi with Stkaes’ contienance evaluation model and contiuned in Teacher Working Group at Nort Jakarta City. The data were collected through participant observation using interviewobservation document study and questionare.The result of the study showed that at the antecedent level there was stell lack of suffort from ical government such as prowding recource persons gudance and finding at transaction level at the showed that the planning and implementation of continuing professional development was not based on the needs of teacher competences and carier and there was no feed back an in continuing and the evaluation of the outcomes level the product of continuing professional development has not been used for upgrading Teachers cariers. The conclusion of the study was that the implementation of the continuing professional development program in Teacher Working Group is less effective and efficien the lock at the local government support to the program icads to an overall in effective and in efficient planning progress, monitoring and evaluation program Allthought the outcomes from the program effech the result of performance appraisal and students achievment it didnot contribute to competencies and carier upgrading, itis recomemded that the local government needs. to improve teachers management and support the program especially in improving techers capital in comprehensive and strategic ways.